Climate change, dengue and the economy ascertaining the link between dengue and climatic conditions - Agustin L. Arcenas (University of the Philippines, School of Economics (UPSE), 2016)
This paper examines the climate-change related factors that affect the incidence of dengue in the Philippines. Dengue, one of the most high-profile public health problems in Southeast Asia, has been estimated to cost hundreds of millions of dollars in the Philippines and worldwide in terms of treatment, surveillance and control, lost income and other indirect costs per year. The disease has been a burden on the public, especially the poor who are less able to access funds for treatment and more heavily affected by the loss in income due to illness. The findings indicate that temperature, precipitation and the incidence of La Ni\~na significantly contribute to the cases of dengue in the Philippines by enhancing the breeding, growth and development of the Aedis aegypti, the dengue-carrying mosquito variety. The econometric results also indicate that better household sanitation practices also reduce dengue cases, indicating that investments to enhance the public's adoption of hygienic and other health practices do lessen the transmission of diseases such as dengue. The results of the study are consistent with the findings of studies regarding dengue in other parts of the world, and contribute to the growing awareness about the health impacts of climate change. This study should provide Philippine policy-makers some guidance in addressing the dengue problem as regional climate change becomes more pronounced.
Keywords: Q54; I18; 330; Dengue; climate change; La Ni\~na